The moderating effect of project complexity on the relationship between organizational controls and cost estimation performance: A conceptual model - M. W., Fazil; Lee, Chia Kuang; P. F. M., Tamyez (IOP Science, 2022)
Cost overrun in construction projects is high and expected to rise. The improvement of cost estimation performance is vital as it provides a better chance for the construction projects to avoid cost blowouts. In this paper, an extensive literature review is conducted from online databases such as Web of Science, Scopus, and Google Scholar which focus on organization controls and its mechanisms to improve cost estimation performance in the construction industry. While many prior studies on cost estimation emphasized investigating cost estimation methods to improve the performance of cost estimation, less attention was given to organizational and project factors. Several studies have explored the effects of organizational control on performance but failed to include project complexity in the relationship between organizational controls and performance. Therefore, this paper conceptualizes the effect of organizational controls on cost estimation performance with project complexity as a moderator. This proposition suggests project complexity has advantages and disadvantages on organizational controls. Each control mechanism has its feature and effectiveness in high complexity projects. Hence, managers should select appropriate control mechanisms, such as input control and output control that have high effectiveness on the performance.